Adobe memories. Assessment and value enhancement of heritage adobe houses in Masaya, Nicaragua - Balmaceda Putoy, Nohemí (2016)
This article is based on the importance of heritage houses, mainly in the house of Ana Maria Vega Fariñas, where the Fariñas family lives. It puts forward that what matters is not only the facade and the environment: a house as a whole goes beyond its location, environment, aesthetics and form, and is always in movement. It is Kevin Lynch who says that the environment influences the assimilation or rejection of a building. Also, any intervention must be designed from the point of view of the user. This point of view should include more than just those who circulate the streets and comes into contact with this place only visually. It should also take into account those who coexist with those walls, who tell their stories and live their lives behind the adobe. This article focuses on the indoor experience; it takes into account that we do not know where we are going but we know where we are coming from.